Strengthening environmental health services delivery through improving data management in South Africa: insights from environmental health managers - Masimula, Siphesihle Siyamukela; Senekane, Mpinane Flory; Naicker, Nisha (Frontiers in Health Services, 2025)
BackgroundIn the delivery of environmental health services (EHS), the data that gets collected provides an opportunity to depict the extent of environmental threats to human health in communities and inform required interventions. In this study, the perspectives and role of environmental health managers in improving data management in the delivery of EHS in municipalities in the KwaZulu-Natal province of South Africa were assessed.MethodsA qualitative phenomenological approach was followed. Data were collected from ten managers via a semi-structured interview guide from February 2024 to April 2024. The transcripts derived from the interviews were analysed via ATLAS.ti version 24.0.0.29576, following which deductive and inductive thematic analysis methods were used.ResultsThe results revealed various roles and responsibilities that environmental health managers play to improve data management and enable insight-driven decision-making. Furthermore, it was shown that through data-driven insights, EHS delivery can be strengthened to be impactful and enable better health outcomes in communities amid existing institutional and technical challenges. This indicated a need for a holistic approach to review and modernise environmental health data management in South Africa to maximise available opportunities.ConclusionIn this juncture, managers have a duty to drive transformation, apply change management and instil a culture of data use in their institutions for impactful service delivery.